Caracterização biomecânica da conduta motora remada básica de passeio do esporte stand up paddle - Praxedes, Jomilto Luiz [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In sport Stand Up Paddle (SUP), the practitioner stands in standing position on the board and use the paddle to move offshore. Despite the increasing number of practitioners as well as the amount of competitions of this sport throughout Brazil, it is not known biomechanical characteristics involved in rowing. This study aimed to characterize biomechanically paddling basic motor conduct SUP sport ride. In this study, 24 cycles of stroke were analyzed. Initially it performed a functional cyclegram of stroke and kinesiology interpretation by ADE® tool through image capture, in sagittal plane, rice paddle. Then in 3D videogrammetric analysis, the images were captured at a frequency of 30Hz, imported to the computer, edited by Virtualdub software and scanned in Skillspector software. In identifying the kinetic behavior of the basic stroke SUP ride kinetic variables were estimated, and the efforts were identified generated in each hand during the stroke, by strain gauges positioned on each handle. It can be identified that 65.8% of the stroke cycle corresponding to the period of propulsion, while the remaining 34.2% corresponding to the recovery period. A higher angular displacement of the shoulder and elbow compared the joints of the spine, hip, knee and ankle. Regarding the kinetic characteristics, it was found that the Kinetic Energy and Momentum increase during stroke, as well as the Work and Impulse were positive. Thus, it can be said that the basic paddling SUP tour is a motor behavior multiplane and the joints of the shoulder and elbow are responsible for rowing movements. It may also be noted that the greatest efforts generated by the performer are identified in the IP, mainly from the beginning to the end of the stroke

No esporte Stand Up Paddle (SUP), o praticante posiciona-se em bipedestação sobre a prancha e utiliza o remo para deslocar-se no mar. Apesar do aumento do número de praticantes assim como da quantidade de competições desta modalidade esportiva no brasileiro, ainda não se sabe das características biomecânicas envolvidas na remada. Assim, este estudo objetivou caracterizar biomecanicamente a conduta motora remada básica de passeio do esporte SUP. Inicialmente foi realizado um ciclograma funcional da remada e interpretação cinesiológica por meio da ferramenta ADE®, mediante captura de imagem, no plano sagital, da remada de passeio. Em seguida, na análise videogramétrica 3D, as imagens foram capturadas a uma frequência de 30Hz, importadas para o computador e digitalizadas no software Skillspector. Na identificação do comportamento cinético da remada básica de passeio SUP, foram estimadas variáveis cinéticas e foram identificados os esforços gerados em cada mão durante a remada, através de extensômetros posicionados em cada pega do remo. Pode-se identificar que 65.8% do ciclo de remada correspondem ao período de propulsão, enquanto que os 34.2% restantes correspondem ao período de recuperação. Observou-se maior deslocamento angular do ombro e do cotovelo, em comparação as articulações da coluna, quadril, joelho e tornozelo. Em relação as características cinéticas, constatou-se que a Energia Cinética e a Quantidade de movimento aumentam durante a remada, assim como o Trabalho e o Impulso foram positivos. Deste modo, pode-se afirmar que a remada básica de passeio do SUP é uma conduta motora multiplanar e que as articulações do ombro e cotovelo são as responsáveis pelos movimentos da remada. Também pode-se observar que os maiores esforços gerados pelo executante são identificados na pega inferior
Biomechanical characteristics of skill motor row ride basic of the sports stand up paddle
Keywords: Biomecânica; Bioengenharia; Movimento; Esportes aquaticos; Biomechanics